Formation of a Covalent Glycosyl–Enzyme Species in a Retaining Glycosyltransferase. Issue 42 (17th September 2013) - Rojas‐Cervellera, Víctor; Ardèvol, Albert; Boero, Mauro; Planas, Antoni; Rovira, Carme
<x xml:space="preserve">Abstract</x> Elusive glycosyl–enzyme adduct: Using classical MD simulations and QM/MM metadynamics, the long‐time sought glycosyl–enzyme covalent intermediate of a retaining glycosyltransferase, with a putative nucleophile residue in the active site, has been trapped (MD=molecular dynamics; QM/MM=quantum mechanics/molecular mechanics).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>